Laser all-ceramic crown removal and pulpal temperature—a laboratory proof-of-principle study. Issue 8 (November 2015) - Rechmann, P.; Buu, N.; Rechmann, B.; Finzen, F.
Abstract The objective of this proof-of-principle laboratory pilot study was to evaluate the temperature increase in the pulp chamber in a worst case scenario during Er:YAG laser debonding of all-ceramic crowns. Twenty extracted molars were prepared to receive all-ceramic IPS E.max CAD full contour crowns. The crowns were bonded to the teeth with Ivoclar Multilink Automix. Times for laser debonding and temperature rise in the pulp chamber using micro-thermocouples were measured. The Er:YAG was used with 560 mJ/pulse. The irradiation was applied at a distance of 5 mm from the crown surface. Additional air–water spray for cooling was utilized. Each all-ceramic crown was successfully laser debonded with an average debonding time of 135 ± 35 s. No crown fractured, and no damage to the underlying dentin was detected. The bonding cement deteriorated, but no carbonization at the dentin/cement interface occurred. The temperature rise in the pulp chamber averaged 5.4° ± 2.2 °C. During 8 out of the 20 crown removals, the temperature rise exceeded 5.5 °C, lasting 5 to 43 s (average 18.8 ± 11.6 s). A temperature rise of 11.5 °C occurred only once, while seven times the temperature rise was limited to 6.8 ± 0.5 °C. Temperature rises above 5.5 °C occurred only when the laser was applied from one side and additional cooling from the side opposite the irradiation. Er:YAG laser energy can successfully be used to efficiently debond all-ceramic crowns from natural teeth. Temperature rises exceeding 5.5 °C only occur when an additional air/water cooling from a dental syringe is inaccurately directed. To avoid possible thermal damage and to allow further heat diffusion, clinically temperature-reduced water might be applied.